Improved detection of myocardial damage in sarcoidosis using longitudinal strain in patients with preserved left ventricular ejection fraction. Issue 9 (September 2016) - Murtagh, Gillian; Laffin, Luke J.; Patel, Kershaw V.; Patel, Amit V.; Bonham, Catherine A.; Yu, Zoe; Addetia, Karima; El‐Hangouche, Nadia; Maffesanti, Francesco; Mor‐Avi, Victor; Hogarth, D. Kyle; Sweiss, Nadera J.; et al.
Abstract : Background: Cardiac infiltration is an important cause of death in sarcoidosis. Transthoracic echocardiography (TTE) has limited sensitivity for the detection of cardiac sarcoidosis (CS). Late gadolinium enhancement (LGE) cardiovascular magnetic resonance (CMR) is used to diagnose CS but has limitations of cost and availability. We sought to determine whether TTE‐derived global longitudinal strain (GLS) may be used to identify individuals with CS, despite preserved left ventricular ejection fraction (LVEF), and whether abnormal GLS is associated with major cardiovascular events (MCE). Methods: We studied 31 patients with biopsy‐proven extra‐cardiac sarcoidosis, LVEF>50% and LGE on CMR (CS+ group), and 31 patients without LGE (CS− group), matched by age, sex, and severity of lung disease. GLS was measured using vendor‐independent speckle tracking software. Parameters of left and right ventricular systolic and diastolic function were also studied. Receiver‐operating characteristic curves were used to identify GLS cutoff for CS detection, and Kaplan–Meier plots to determine the ability of GLS to predict MCE. Results: LGE was associated with reduced GLS (−19.6±1.9% in CS− vs −14.7±2.4% in CS+, P <.01) and with reduced E/A ratio (1.1±0.3 vs 0.9±0.3, respectively, P  =.01). No differences were noted in other TTE parameters. GLS magnitude inversely correlated with LGE burden ( r =−.59). GLS cutoff of −17% showed sensitivity and specificity 94% for detecting CS. Patients who experienced MCE had worse GLS than those who did not (−13.4±0.9% vs −17.7±0.4%, P =.0003). Conclusions: CS is associated with significantly reduced GLS in the presence of preserved LVEF. GLS measurements may become part of the TTE study performed to screen for CS.